Market Basket Analysis using the Frequent Pattern Growth Algorithm at RJ Mart Melaris - arrafiq, ubay hakim; Azhar, Yufis; Wicaksono, Galih Wasis (Sistemasi: Jurnal Sistem Informasi, 2024)
Marketing strategy in a business is a major factor in the success or failure of a business both micro, medium and macro. With an effective and efficient marketing strategy It is hoped that it can increase income to the maximum. Currently, technological developments are very fast, including carrying out transactions that are directly connected to the database, resulting in very large data growth. The data itself can be used as a source of information to determine the right marketing strategy. The main aim of this research is to maximize the existing marketing strategy at RJ Mart Melaris by utilizing data as a source of information and consideration. The choice of Market Basket Analysis as a method for utilizing data is because these medium-sized businesses need consideration to develop sales by forming effective product packages. Frequent Pattern Growth is used as an effective algorithm to form combinations of product items or what is usually called an association rule. Some of the benefits resulting from this research are knowing how likely a product is to be purchased at the same time as other products, what products are sold the most and the least so that you can maximize stock of goods, and the relationship between products to maximize the placement of goods. This research produced 8 Association Rules or product combinations with 6 different items. The strongest rule that is generated is that if you buy special fried Indomie and chicken curry Indomie, you will definitely also buy special chicken Indomie with an association strength of 8,472. Meanwhile, the item that is most often purchased together with other items is the special fried Indomie, which sells 50% together with the special chicken curry Indomie and special chicken Indomie. Apart from that, this research also produced 2 different groups of items, each item in the group has a sales relationship.